ASSESSMENT AND STATISTICAL ANALYSIS OF THE CONCENTRATIONS OF DISSOLVED METALS IONS IN SELECTED SURFACE WATER BODIES IN ZARIA (FUDMA JOURNAL OF SCIENCES, 2024)
The surface water bodies in Zaria, Kaduna State, Nigeria, are vital for supporting the local ecosystem and providing water resources for various human activities. However, increasing industrialisation and urbanisation in the region have raised concerns about the potential impact of metal pollution on these water bodies. This study investigates the composition of dissolved metals, including Pb, Cu, Co, Ni, and Cd, in three surface water bodies: Shika Dam, Gamma Dam, and ABU Dam. Atomic Absorption Spectroscopy (AAS) was utilised to detect the presence of these metals, followed by systematic calculations of correlation coefficients to simplify the interpretation of the data. The ANOVA conducted at a 95% confidence level indicated no significant differences in the analysed metal concentrations across all sampling points (p > 0.05), suggesting a common source of pollution. The concentrations of Pb, Cu, and Co were found to be below the detection limit. Correlational analysis revealed strong positive correlations between Pb and Cu (r = 0.999, 0.998) at sampling points 2 and 6, indicating a shared source of contamination, while negative correlations (r = -0.998, -1) at points 9 and 6 suggested indicate differing environmental conditions. Additionally, a perfect positive correlation (r = 1) between Cu and Co points to a single source, likely related to industrial activities. Similarly, there were strong correlations between Cd and Co, as well as between Cd and Cu. These findings show the complex interrelationships within aquatic ecosystems and highlight the need for holistic water quality management.
Keywords: Surface water; Water pollution; Dissolved metal ions; Statistical analysis; Atomic absorption spectroscopy